Systematic Pharmacology-Based Strategy to Explore the Mechanism of Bufei Huoxue Capsule in the Treatment of Chronic Obstructive Pulmonary Disease. (6th December 2022) - Shi, Liangtian; Yan, Jun; Meng, Yufeng; Wang, Guishu; Du, Jianchao; Feng, Cuiling
Abstract : Objective . To explore the effects and mechanisms of Bufei Huoxue Capsule (BHC) on chronic obstructive pulmonary disease (COPD) based on network pharmacology. Methods . The effective components and related targets of BHC were collected by searching TCMSP, HERB, and ETCM databases, after which the related targets of COPD were obtained on GeneCards and OMIM databases. The common targets were imported into the STRING database and Cytoscape database to construct a target interaction network and screen core targets. Next, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed on the Metascape platform. According to the prediction results of network pharmacology, the action mechanism was further examined in an animal model of COPD. The pathological changes of lung tissue were observed by HE staining; goblet cells and mucus secretion in lung tissue were observed by AB-PAS staining, airway collagen deposition was observed by Masson staining, and the expression of NE, TGF- β 1, P-EGFR/EGFR, P-ERK1/2/ERK1/2, P-JNK/JNK, and P-P38/P38MAPK protein was detected by Western blot analysis. Results . A total of 379 targets related to BHC and 7391 targets related to COPD were obtained, including 313 potential targets of BHC in treating chronic obstructive pulmonary disease, with JUN, AKT1, TNF, IL6, EGFR, MAPK1, and MAPK14 as the core targets. Through enrichment analysis, BHC may interfere with COPD by regulating the MAPK signal pathway, HIF-1 signal pathway, NF- κ B signal pathway, cAMP signal pathway, cGMP-PKG signal pathway, and so on. Animal experiments showed that the BHC could reduce airway inflammatory cell infiltration, inhibit airway epithelial goblet cell proliferation, reduce mucus secretion, and improve small airway collagen fiber deposition in COPD model rats. Besides, BHC could downregulate the protein expression of NE, TGF- β 1, P-EGFR, P-ERK1/2, and P-P38MAPK. Conclusion . BHC can reduce airway inflammation, inhibit mucus hypersecretion, and improve airway remodeling by regulating the MAPK signal transduction pathway.